Perubahan Livelihood Masyarakat Setelah Tinggal di Rumah Susun Sederhana Sewa (Studi Kasus: Rusunawa Sejuta Kanal, Kabupaten Indragiri Hilir, Riau) - Afriansyah, Faizal; Urifi, Zulfadly (REKSABUMI, 2024)
Flats located in Indragiri Hilir Regency were built with the aim of relocating low-income people who live on the banks of the Indragiri River. The procurement of Rusunawa is expected to improve people's quality of life. However, some of the procurement of Rusunawa did not have an impact on improving the quality of life (Livelihood) of the residents. Research is needed to identify changes in people's Livelihood after living in Rusunawa. The purpose of this study is to identify changes in the Livelihood of residents of low-cost flats for rent after moving to simple flats for rent through the Sustainable Urban Livelihood (SUL) approach. This research can be used as material for the Government's evaluation to determine the level of success of the programs that have been built. The analysis used is the analysis of 5 Livelihood assets with the Paired Sample T-Test method. Based on the results of analyzing Livelihood quality before and after resettlement of 5 Livelihood assets, namely human, natural, social, physical, and financial assets, it can be concluded that there has been a change in the form of an increase in Livelihood quality. In addition, after further analysis using the Paired Sample T-Test, it was found that there was a significant change from moving residence to changes in the quality of community Livelihood. So it means that the quality of Livelihood of the people of simple rented flats can be said to be good because they are able to provide changes for the better.